Engineering and Durability Properties of Sustainable Bricks Incorporating Lime Kiln Dust, Ground Granulated Blast Furnace Slag, and Tyre Rubber Wastes - Joy Ayankop Oke; Hossam Abuel-Naga (Buildings, 2025)
This study explores the potential of using sustainable materials in brick manufacturing by designing a novel brick mix in the laboratory, incorporating sand, lime kiln dust (LKD) waste, tyre rubber, and ground granulated blast furnace slag (GGBFS) waste. These cementless bricks blended LKD–GGBFS wastes as the binder agent and fine crumb rubber from waste tyres as a partial replacement for sand in measured increments of 0%, 5%, and 10% by volume of sand. Ordinary Portland cement (OPC) and fired clay bricks were sourced from the industry, and their properties were compared to those of the laboratory bricks. Tests performed on the industry and laboratory bricks included compressive strength (CS), freeze-thaw (F-T), and water absorption (WA) tests for comparison purposes. Additionally, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) analyses were performed on the bricks to assess the morphological and mineralogical changes responsible for the observed strengths and durability. The CS and WA values of the engineered bricks were 12, 6, and 4 MPa, and 7, 12, and 15%, respectively, for 0, 5, and 10% crumb rubber replacements. The industry bricks’ average CS and WA values were 13 MPa and 8%, respectively. From the results obtained, the green laboratory bricks passed the minimum strength requirements for load-bearing and non-load-bearing bricks, which can be used to construct small houses. Lastly, the engineered bricks demonstrated strength and durability properties comparable to those of the industry-standard bricks, indicating their potential as a sustainable alternative to help divert waste from landfills, reduce the pressure on natural fine sand extraction, and support eco-conscious brick production for a sustainable environment.